On the Guarantee of the Realization of the Right to Education - Elena A. Kashtanova (Сибирское юридическое обозрение, 2017)
The article reveals the issues of the essence and content of the guarantee of the realization of the right to education, the system of guarantees for the implementation of constitutional and legal principles and norms, including those that consolidate the system of rights and freedoms of human and citizen. The Author examines the functions of guarantee (stimulating, law enforcement and law enforcement), analyzes types of guarantees - guarantees related to the very right to education and quality of education.